Acute generalized exanthematous pustulosis induced by ceftriaxone with positive patch testing - Ana Gabriela Lopes; Carmem Botelho; Lise Brosseron (Alergologia Polska)
Acute generalized exanthematous pustulosis (AGEP) is a rare severe cutaneous reaction. In over 90% of patients it is an adverse reaction to drugs. Delayed-type (type IV) hypersensitivity seems to play an important role in its pathophysiology. Positive patch tests have ranged from 18% to 75%, with 93 culprit drugs identified. Our case involves an 87-year-old female patient, treated for a periprosthetic joint infection with ceftriaxone and daptomycin, who developed acute generalized exanthematous pustulosis. Clinical diagnosis was confirmed by skin biopsy. Patch testing performed five months later confirmed sensitization to ceftriaxone. Patch testing is useful to identify the cause of AGEP when the responsible drug is unclear.